Bilingualism-Based Teaching Language on English Class at Senior High School - Ika Isra Ayu; Kisman Salija; Geminastiti Sakkir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aims to determine how bilingualism is applied in terms of management and instructional talk in Senior High School English classes. At a senior high school, the researchers did this study (SMA 2 Bantaeng). A class observation guide served as the researcher's research tool to collect the data. According to the study's findings, teachers 1 and 2 do not always employ instructional talk. While Teacher 2 only utilized four of the five types of instructional discussion, teacher 1 employed all five types. Teachers 1 and 2 each employ 10 different types of management talks, while the total number of management talk types is 15. Teacher 2 utilizes 11 different types of management talks.